(untitled) (Research, Society and Development, 2021)
Aim of this study was to analyze the effects of osteoporosis onset in postmenopausal women, as well as its influence on the survival of dental implants in this group of women. The literature review was carried out through a literature review of studies published in recent years in the databases of PubMed/Medline, Scopus, LILACS and SciELO. The results indicated that osteoporosis directly affects the maxillary bones, causing changes in their bone quality and density. However, these changes did not affect the survival rate of dental implants in this female group, which was also observed in relation to the use of oral bisphosphanes. It is possible to conclude that osteoporosis caused by menopause causes bone changes in the jaws, but does not affect the survival of dental implants. The same occurs in women who use oral bisphosphonates.